The Effect of Internationalization on Bank Performance in Republic of Korea - Muhammad Faruq Abdulhakim; Chandra Utama (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2023)
The goal of this paper is to discover the effect of internationalization on bank performance of 8 internationalized commercial banks from Republic of Korea (ROK). Resource-based view is applicated as theoretical framework. To reach the goal, this research used panel data regression by fixed effect model. The dependent variable of this research is ROA. Meanwhile the independent variables are number of foreign presences, TNI, and South Korea’s macroeconomic conditions. The research using secondarily data that collected from FSS of ROK and BOK. The result reveals that internationalization gives positive effect to the performance of the commercial bank in ROK.